2021
DOI: 10.1371/journal.pone.0246343
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of MRSA nasal carriage among pregnant women in Copenhagen

Abstract: Background Methicillin resistant Staphylococcus aureus (MRSA) frequently causes outbreaks in neonatal intensive care units (NICUs). It is believed that MRSA predominantly enters the NICU with MRSA colonized parents. In Denmark, 27 MRSA NICU outbreaks have been registered between 2008 and 2019. Aim The aim of this study was to determine the prevalence of MRSA nasal carriage in pregnant women in Copenhagen and to clarify if MRSA screening during pregnancy could add to the prevention of NICU outbreaks. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The introduction of MRSA to the NICU by colonized parents has often been discussed. The risk for introduction might vary due to the heterogeneous geographical MRSA burden; for instance, a very low MRSA prevalence among pregnant women was recently reported in Denmark [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of MRSA to the NICU by colonized parents has often been discussed. The risk for introduction might vary due to the heterogeneous geographical MRSA burden; for instance, a very low MRSA prevalence among pregnant women was recently reported in Denmark [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have not been many reports of TSS due to postpartum MRSA, routine anti-MRSA therapy is not recommended [ 26 ]. The possibility of infections in pregnant women during hospitalization after delivery has been reported to be 0.11% [ 73 ], and it is essential to consider the risk factors for MRSA infection in each healthcare setting. Therefore, anti-MRSA therapy should be evaluated based on each patient’s risk factors or in cases where MRSA colonization has already been observed in the past [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we compared the prevalence of staphylococcal isolates recovered in patients of the African study with a history of vaginitis/ discharge, 66/146, i.e., 45.2% (p= 0.05) and the Chinese study reported 4/150, i.e., 2.7% (p= 0.81). A cross-sectional study conducted in Copenhagen, Denmark in 2021 (n=1778) reported quite contrasting results compared to the above Chinese and African reports [ 8 ]. Only two women, i.e., 0.11% were found to harbor MRSA .…”
Section: Reviewmentioning
confidence: 99%
“…Though it is widely hypothesized that outbreaks of MRSA infections primarily occur in the NICU after contact with colonized mothers or have been a nosocomial infection [ 8 ], recent studies have shown that infections have occurred and can occur even without exposure to healthcare settings or healthcare workers [ 9 ]. Reported data suggest that infant and maternal colonization of MRSA in the USA alone ranges from 1% to 4% which varies across different parts of the country, and it has also been stated that women of African ethnicity are more likely to have higher rates of colonization [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%